1975
DOI: 10.1136/pgmj.51.601.795
|View full text |Cite
|
Sign up to set email alerts
|

The influence of nutritional factors on lead absorption

Abstract: SummaryThe nutritional factors which affect lead absorption have been studied. Synthetic diets of known composition were compounded to contain 0-075% Pb as PbCl2 labelled with 203Pb. Rats were exposed to lead for periods of 48 hr. The dietary intake was then measured and the absorption of lead determined by means of a whole-body counter. Lead absorption was increased by high fat, low mineral, low protein and high protein diets but was decreased by high mineral diet. Low fat, low fibre, high fibre, low vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0
3

Year Published

1987
1987
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(69 citation statements)
references
References 15 publications
4
62
0
3
Order By: Relevance
“…Previous human epidemiologic studies and experimental animal studies support this finding (Barltrop and Khoo 1975;Bell and Spickett 1983;DeLuca et al 1982;Lucas et al 1996;Mahaffey 1995). A possible mechanism by which dietary fat increases lead absorption involves the stimulation of bile secretion into the gastrointestinal tract by fat (Bell and Spickett 1983;Hilburn et al 1980;Lucas et al 1996).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Previous human epidemiologic studies and experimental animal studies support this finding (Barltrop and Khoo 1975;Bell and Spickett 1983;DeLuca et al 1982;Lucas et al 1996;Mahaffey 1995). A possible mechanism by which dietary fat increases lead absorption involves the stimulation of bile secretion into the gastrointestinal tract by fat (Bell and Spickett 1983;Hilburn et al 1980;Lucas et al 1996).…”
Section: Discussionsupporting
confidence: 69%
“…These patterns persisted for both males and females as well as for younger children (< 12 months of age) and for older children (12 months of age or older; data not shown for age). To our knowledge, there have been no other human studies investigating whether caloric intake modifies the association between dust lead exposure and blood lead; however, this modification is supported by data from animal studies (Barltrop and Khoo 1975;Bell and Spickett 1983;DeLuca et al 1982;Kello and Kostial 1973;Nzelibe et al 1986). In addition, findings from human studies have been reported for the association between caloric intake and blood lead.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Vários estudos experimentais investigaram o papel do estado nutricional na absorção e toxidez do chumbo 2,10,18 , partindo de clássicas observações clínicas que revelaram que crianças intoxicadas pelo chumbo eram geralmente desnutridas 8 . Existem poucos estudos relacionando a absorção de cádmio e desnutrição em crianças 3,10 .…”
Section: Introductionunclassified
“…Adults absorb roughly 10% of the total amount of lead ingested in the diet (Barltrop and Khoo, 1975;Heard and Chamberlain, 1982), although other studies suggest that absorption may be as high as 15-20% (Duggan, 1983). On the other hand, in infants less than 2 years old, 42% of dietary lead was absorbed with intakes =5 Jlg Pb/kg bodyweight (bw) (Ziegler et al, 1978).…”
Section: Introductionmentioning
confidence: 99%